IMPLICATIONS OF THE ISRAEL - IRAN CONFLICT ON COMMODITY-BASED INVESTMENT AND PORTFOLIO DIVERSIFICATION - Pandin, Maria Yovita R; Nurrochmah, Aliatus; Rahmawati, Septiana Rozzi (Universitas 17 Agustus 1945 Surabaya, 2024)
This study examines the effects of the Israel-Iran conflict on commodity-based investments and portfolio diversification on a global scale. The primary aim of this research is to assess how the conflict influences commodity investments and portfolio diversification strategies. The study adopts a mixed-methods approach, integrating both quantitative and qualitative analyses. The quantitative analysis utilized secondary data, including geopolitical ratios and crude oil prices, sourced from the geopolitical risk index and Investing.com. On the other hand, the qualitative analysis involved distributing questionnaires via Google Forms to selected participants, with the primary criterion being their status as investors. The results of hypothesis testing showed that none of the proposed hypotheses were supported. These findings suggest no significant relationships between the variables analyzed: the Israel-Iran conflict does not significantly impact portfolio diversification, portfolio diversification does not significantly influence commodity-based investments, and the Israel-Iran conflict does not have a meaningful effect on commodity-based investments. The study concludes that, within the context of this research, the examined variables do not demonstrate a statistically significant relationship.